Pelatihan Pendidikan Jasmani untuk Meningkatkan Literasi Fisik Jenjang Anak Usia Dini - Eka Arisandi, Rendis (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Physical education has a very important role in forming the basis for the physical development of early childhood. Physical literacy, which refers to the knowledge, skills and beliefs that enable individuals to engage in physical activities effectively and happily, is a key foundation in supporting children's physical and cognitive development. This article aims to examine how physical education training can improve physical literacy in early childhood. With an approach based on the development of fine and gross motor skills, as well as an understanding of the importance of physical activity for long-term health, physical education training is expected to shape the character of children who are healthy, active and have good motor skills.